Dielectric and flexoelectric deformations induced by ac electric field in insulating nematic layers - Derfel, Grzegorz; Buczkowska, Mariola; Guzowski, Jakub (Wydawnictwo Politechniki Łódzkiej, 2010)
The deformations of homeotropic nematic layers induced by ac electric field of frequency f were studied numerically. Two kinds of nematic liquid crystals with small negative dielectric anisotropy, Δε < 0, were considered: (i) the non-flexoelectric nematic, (ii) the nematic characterised by the positive sum of flexoelearic coefficients e = e11 + e33 > 0. It was found that at sufficiently low frequencies, the deformations varied with time. The deformations of purely dielectric nature had the period l/(2f). The time period of flexoelectric distortions was equal to 1/f. The influence of rotational viscosity and of thickness of the layer on the dynamics of deformations was analysed.

Zbadano numerycznie odkształcenia homeotropowych warstw nematyków wywołane zmiennym polem elektrycznym o częstości f. Rozpatrzono dwa rodzaje nematycznego ciekłego kryształu o malej anizotropii dielektrycznej Δε < 0: nematyk pozbawiony właściwości fleksoelektrycznych oraz nematyk scharakteryzowany dodatnią sumą współczynników fleksoelektrycznych e=e11+e33 > 0. Stwierdzono, że przy dostatecznie niskiej częstości odkształcenie zmienia się okresowo z czasem. Okres deformacji czysto dielektrycznych wynosi l/(2f), a deformacji o naturze fleksoelektrycznej równy jest l/f. Przeanalizowano wpływ lepkości rotacyjnej i grubości warstwy na dynamikę odkształceń.
Dielektryczne i fleksoelektryczne odkształcenia warstw nematycznych wywołane zmiennym polem elektrycznym